Reduction in chloroplastic ribulose-5-phosphate-3-epimerase decreases photosynthetic capacity in Arabidopsis - Li, Yonghong; Peng, Lianwei; Wang, Xiaoqin; Zhang, Lin (Frontiers in Plant Science, 2022)
Chloroplast ribulose-5-phosphate-3-epimerase (RPE) is a critical enzyme involved in the Calvin-Benson cycle and oxidative pentose phosphate pathways in higher plants. Three Arabidopsis rpe mutants with reduced level of RPE were identified through their high NPQ (nonphotochemical quenching) phenotype upon illumination, and no significant difference of plant size was found between these rpe mutants and WT (wild type) plants under growth chamber conditions. A decrease in RPE expression to a certain extent leads to a decrease in CO2 fixation, Vcmax and Jmax. Photosynthetic linear electron transport was partially inhibited and activity of ATP synthase was also decreased in the rpe mutants, but the levels of thylakoid protein complexes and other Calvin-Benson cycle enzymes in rpe mutants were not affected. These results demonstrate that some degree of reduction in RPE expression decreases carbon fixation in chloroplasts, which in turn feedback inhibits photosynthetic electron transport and ATP synthase activity due to the photosynthetic control. Taken together, this work provides evidence that RPE plays an important role in the Calvin-Benson cycle and influences the photosynthetic capacity of chloroplasts.